Interbank lending and monetary policy transmission - evidence for Germany - Michael Ehrmann; Andreas Worms (European Central Bank (ECB), 2001)
This paper presents empirical evidence on the behaviour of interbank lending in Germany after a monetary policy impulse. Our VAR analysis shows that following a monetary contraction, the banking system as a whole attracts additional funds from foreign banks. Whereas small cooperative and savings banks do not seem to directly access the interbank market themselves, they do so indirectly through the head institutions of their sectors, i.e. the savings banks` and credit cooperative sector, respectively. The interbank flows within these two sectors allow small banks to access funds that might help them in keeping their loan portfolio relatively unaffected. This may explain why the evidence for a bank lending channel in Germany seems to be weaker compared to other countries, e.g. the US.
Keywords: C32; E52; G21; 330; bank lending channel; Interbank Market; monetary policy